String cosmological models of Bianchi type-III - Singh J.K.; Ram S. (My University, 2025)
A technique to generate new exact Bianchi type-III cosmological solutions of massive strings in the presence of magnetic field is presented. Starting from Tikekar and Patel's strings models in the absence and presence of the magnetic field, new solutions are obtained. Some of their physical features are discussed.